2010
DOI: 10.4067/s0716-97602010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of some marine brown algae against cancer cell lines

Abstract: The aim of this study was to investigate the in vitro cytotoxic activity of total extract of MeOH (70%) and partition fractions of hexan, chloroform (CHCL 3) , ethylacetate (EtOAc) and MeOH-H 2 O of brown algae species (Sargassum swartzii, Cystoseira myrica, Colpomenia sinuosa) found in the Persian Gulf against in different cell lines including HT-29, Caco-2, T47D, MDA-MB468 and NIH 3T3 cell lines by MTT and AnnexinV-PI assay. The hexan fraction of S. swartzii and C. myrica showed selective cytotoxicity agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 12 publications
2
46
0
2
Order By: Relevance
“…For instance, C. tamariscifolia extract exhibited strong cytotoxic activity against Daudi, Jurkat and K562 tumor cell lines [30]. The hexane fraction of the methanolic extract from C. myrica (S.G.Gmelin) C. Agardh showed an interesting activity against T47D (breast carcinoma) (IC 50 = 99.9 μg/mL) and mainly against MDA-MB468 (breast carcinoma estrogen receptor independent (IC 50 = 56.5 μg/mL) [11]. Also, the dichloromethane extract of fresh C. abiesmarina displayed selective and antiproliferative activity against HeLa cell line, induced by apoptosis (IC 50 = 8.8 μg/ mL) [2].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, C. tamariscifolia extract exhibited strong cytotoxic activity against Daudi, Jurkat and K562 tumor cell lines [30]. The hexane fraction of the methanolic extract from C. myrica (S.G.Gmelin) C. Agardh showed an interesting activity against T47D (breast carcinoma) (IC 50 = 99.9 μg/mL) and mainly against MDA-MB468 (breast carcinoma estrogen receptor independent (IC 50 = 56.5 μg/mL) [11]. Also, the dichloromethane extract of fresh C. abiesmarina displayed selective and antiproliferative activity against HeLa cell line, induced by apoptosis (IC 50 = 8.8 μg/ mL) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Also, three algae extracts, have demonstrated cytotoxic activity, from the crude extracts of 21 brown algae collected from the south coast of England and the West coast of Ireland (Spavieri et al 2010). The methanol extract of Sargassum swartzii collected from the Persian Gulf showed cytotoxic effect against T-47D cells (IC 50 \ 100 lg/ml) (Khanavi et al 2010). The study of Burt (2004), has shown that minor components play a role in the antibacterial activity, possibly by producing synergistic effects with other components.…”
Section: Discussionmentioning
confidence: 99%
“…The various biological properties exhibited by brown algae include immune modulation (Raghavendran et al, 2011); anti-inflammation (Islam et al, 2013); antiviral (Sinha et al, 2010); antioxidative (Balboa et al, 2013);vasodilation (Park et al, 2008); anticoagulant (Arivulsevan et al, 2011); antitumor (Khanavi et al, 2010); anti-vasculogenic (Dias et al 2008); antiherpetic (Lee et al, 2010) anti lipidemic (Guangling Jiao et al, 2011), and hepato-protection (Josephine et al, 2008). Brown algae have potential for therapeutic application because they are taxonomically diverse, largely productive, biologically active and chemically unique, thus offering a great scope for discovery of drugs from the ocean.…”
Section: Brown Algaementioning
confidence: 99%